Power Flow Solution for Unbalanced Distribution Networks with Distributed Generator Using Sweep Method and Improved Compensation Technique - Blanco, Gabriel O. [UNESP]; Leite, Jonatas Boas (Institute of Electrical and Electronics Engineers (IEEE), 2025)
In unbalanced distribution networks with radial topology, the use of sweeping methods is advantageous compared to traditional methods for solving power flow. Therefore, in this work, the well-known bi-quadratic equation for the nodal voltage magnitude through branch power flow is expanded to the threephase distribution networks. As the sweep methods deal well with distribution network ill-conditions, due to their simplicity and fast convergence, further studies, variations, and enhancements of the algorithm have been constantly done. In order to increase the algorithm efficiency in terms of computational performance, the compensation technique for voltage-controlled nodes is also improved with the Newton-Raphson approach. To verify performance improvement, the proposed algorithm is evaluated in a 135 bus test network with radial topology and several electrical devices installed, such as capacitors, voltage regulators, and distributed generators. The results show the accuracy of the three-phase formulation and a better computational performance of the proposed compensation approach with a gain around 57 %.